The arduino based prototype of handsanitizer tool and automatic mask feeder - Syahrial Syahrial; Muhammad Fajrin S; Yusuf Syani (Labor Dasar dan Sentral Universitas Andalas, 2020)
The purpose of this research is to design and construct a prototype of an Arduino-based automatic handsanitizer and mask feeder. The research method was carried out by laboratory experiments. The experimental stages consisted of designing hardware (hadware), software (software) and testing the whole tool. The test results showed that ultrasonic sensor and dispencer can detect at a distance of 5 cm. The Arduino dc motor test that given high and low logic for the direction of each clockwise and counter clockwise motor resulted in an output voltage of 5.09V. Overall the tool testing went well. Regarding to the results, it can be concluded that the tools can be on of the options to reduce the spread of COVID-19 in the Jakarta State University academic community, especially the laboratories within the Jakarta State University.